2013
DOI: 10.1016/j.febslet.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Circadian gene Clock contributes to cell proliferation and migration of glioma and is directly regulated by tumor‐suppressive miR‐124

Abstract: a b s t r a c tAlthough the roles of circadian Clock genes and microRNAs in tumorigenesis have been profoundly studied, mechanisms of cross-talk between them in regulation of gliomagenesis are poorly understood. Here we show that the expression level of CLOCK is significantly increased in high-grade human glioma tissues and glioblastoma cell lines. In contrast miR-124 is attenuated in similar samples. Further studies show that Clock is a direct target of miR-124, and either restoration of miR-124 or silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 37 publications
1
66
0
Order By: Relevance
“…Although some studies indicate that specific clock genes may act as tumor suppressors (Fu et al, 2002), other studies suggest a more complex relationship between the circadian rhythm and cancer (Antoch et al, 2013). Our finding that AML cells require Clock and Bmal1 expression reinforces recent work demonstrating tumor-maintaining roles for the core circadian rhythm genes in a variety of cancers (Antoch et al, 2008; Cui et al, 2015; Elshazley et al, 2012; Janich et al, 2011; Li et al, 2013; Ozturk et al, 2009; Xiao et al, 2014). …”
Section: Discussionsupporting
confidence: 88%
“…Although some studies indicate that specific clock genes may act as tumor suppressors (Fu et al, 2002), other studies suggest a more complex relationship between the circadian rhythm and cancer (Antoch et al, 2013). Our finding that AML cells require Clock and Bmal1 expression reinforces recent work demonstrating tumor-maintaining roles for the core circadian rhythm genes in a variety of cancers (Antoch et al, 2008; Cui et al, 2015; Elshazley et al, 2012; Janich et al, 2011; Li et al, 2013; Ozturk et al, 2009; Xiao et al, 2014). …”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, it appears that circadian genes are to some extent related to glioma risk and outcome [66]. In particular elevated levels of CLOCK contribute to cell proliferation and migration in glioma [67]. Of note is that Clock is directly regulated by REV-ERBα [45] and therefore agonists for REV-ERBα [4] may not only reduce Fabp7 expression but also Clock levels, which may reduce neurogenesis and lower the potential of glioblastoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Many miRNAs have been proved to be proto-oncogenes or tumor suppressors in various human cancers, including in glioma. [3][4][5] Recent studies have revealed that miRNAs, such as miR-7, 6, 7 miR-124, [8][9][10] miR-128, 11 miR-107, 12 and miR-181b, [13][14][15] are globally dysregulated in glioma. However, the particular molecular mechanisms through which miRNAs mediate glioma carcinogenesis and metastasis are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%